KEDUDUKAN HUKUM PERJANJIAN PERKAWINAN YANG DIBUAT SETELAH PERKAWINAN TERHADAP PIHAK KETIGA (Pasca Putusan Mahkamah Konstitusi Nomor. 69/PUU-XIII/2015) - kusuma, candra hadi (JURNAL HUKUM dan KENOTARIATAN, 2018)
AbstrakPerjanjian perkawinan yang dibuat setelah perkawinan pasca putusan MK no.69/PUU-XIII/2015 membawa akibat terhadap perubahan status hukum harta benda yang terdapat atau diperoleh di dalam perkawinan. Bagi pihak ketiga yang menjadi kreditur, adalah penting untuk mengetahui bagaimana kedudukan harta kekayaan suami-istri. Hal ini berkait dengan kepastian terlunasinya piutang. Jika suami-istri kawin dengan persatuan bulat harta kekayaan perkawinan, maka utang yang dibuat oleh suami-istri dapat dituntut pelunasannya dari harta persatuan. Sebaliknya jika terdapat Perjanjian Kawin maka pelunasan utang menjadi tanggung jawab pihak yang membuat perjanjian. Kedudukan hukum perjanjian perkawinan yang dibuat setelah perkawinan terhadap pihak ketiga kekuatan mengikatnya adalah terhitung sejak didaftarkan. Dalam hubungannya dengan pihak ketiga, perjanjian kawin tersebut mengikat kedepan dan tidak berlaku surut.Kata Kunci : Perjajian Perkawinan, Kedudukan Hukum,Perlindungan Hukum AbstractThe marriage agreement made after the marriage after the Constitutional Court's decision no.69 / PUU-XIII / 2015 has brought about a change in the legal status of the property contained or obtained in the marriage. For third parties who become creditor, it is important to know how the position of husband and wife property. This is related to the certainty of the settlement of receivables. If married couples with unanimous union of marriage property, then the debt made by the husband and wife can be demanded of repayment from the property of unity. Conversely, if there is a Marriage Agreement then debt repayment becomes the responsibility of the party making the agreement. The legal status of a marriage agreement made after marriage against a third party of binding force shall be effective as of the date of registration. In conjunction with a third party, the marriage agreement is binding to the fore and is not retroactive.Legal protection for third parties in the marriage agreement there are two forms of preventive legal protection by the form of ratification by the marriage or notary and repressive protection by filing a lawsuit to the court.Keywords: Marriage Agreement, Legal Status, Legal Protection